Compliance with the principle of equal treatment in public procurement law through the protection of personal data - Onica, Adriana Iulia; Cătană, Emilia Lucia (International Journal of Legal and Social Order, 2023)
This study aims to summarize the application of the principle of equal treatment in public procurement law within the legislation of the European Union and in the legal system in Romania and also the fair processing of personal data as an expression of the principle of equal treatment by actors involved in public procurement in Romania and in public procurement litigation as reflected in doctrine, legislation and judicial practice. The research method chosen is epistemological and empirical analysis, whilst highlighting legislation incidents pertaining to the chosen subject and of the judicial practice, resulting in the improvement of the research topic addressed, for a better understanding and application of the legal provisions in the matter of respecting the principle of equal treatment and that of protection personal data in public procurement law. In the end, the study highlights the conclusions reported to the analysis of the topic dealt with.